h :: M Int -> M Int -> M Int
h x y = bind ( \x-> g x y ) x
where g is
g :: Int -> W Int -> W Int
g x y = y >>= (return . (+x))
for the monad:
data M a = M a deriving Show
Now I am a little confused, how can you put x in g if it takes an Int
as first parameter but x is M Int
?
Because it's a different "x". Lemme rewrite it slightly:
h :: M Int -> M Int -> M Int
h x y = bind ( \w -> g w y ) x
All I did was replace the inner "x" with "w", to demonstrate that it has no relationship to the outer "x"; the \... -> syntax introduces new local bindings unrelated to any outside of it, in this case for "w" (or what he had "x", shadowing the original binding of "x" within the lambda).
--